The Philosopher in the Eyes of the Sufi: The Place of Ibn Sina in the Thought of Sheikh Ala' al-Dawlah al-Sammani - Ghasem Raufi; Ghodratollah Khayatian; Azim Hamzeian (ادبیات عرفانی)
This paper examines the views of Sheikh Ala al-Dawla Semnani, a jurist and mystic from the 7th and 8th centuries, in his criticism of Avicenna and the philosophers. Semnani adopts a critical and analytical approach and examines the philosophical and mystical foundations. The research employs library-based methods and descriptive-analytical methodology to present Semnani's perspective as a Sufi scholar on Avicenna as a philosopher. In his critique of various theological, philosophical and mystical theories, Semnani raises serious objections to Avicenna's views and categorizes him among the philosophers and followers of Greek wisdom. Semnani claims that the philosophers' statements are often erroneous and baseless, primarily relying on reason and contradict Sunni orthodoxy. He engages with Avicenna's ideas on four central themes: God's knowledge of the particulars, the eternity of the world, the denial of bodily resurrection, and the soul's pleasure and suffering in the afterlife, responding to them according to his theological-mystical approach. The examination reveals fundamental differences between Semnani's and Avicenna's theological and philosophical approaches. As a mystic-theologian, Semnani emphasizes religious doctrines, affirming God's comprehensive knowledge and the temporal creation of the world, while Avicenna adopts a philosophical and liberal approach with his universal interpretation of God's knowledge and emphasis on the complexities of creation and spiritual resurrection.